Biodegradable nano carbon-based smart filters for efficient remediation of pharmaceutical contaminants. Issue 45 (5th November 2018) - Tripathi, Indu; Dodgen, Laurel K.; Ostadhossein, Fatemeh; Misra, Santosh K.; Daza, Enrique; Sharma, Brajendra K.; Zheng, Wei; Pan, Dipanjan
Abstract : Emerging chemical contaminants such as pharmaceutical residues in water resources continue to threaten the homeostasis of our ecosystem. Here a carbon based nanoplatform is developed to provide a desirable solution. Abstract : Emerging chemical contaminants such as pharmaceutical residues in water resources continue to threaten the homeostasis of our ecosystem. We have developed a 'smart-filter' comprising tunable, biodegradable, and commercially amenable pharmaceutical-nano-carbon-scavengers (PNCSs) to efficiently and safely remediate pharmaceutical residues. The PNCS particles successfully removed 63.5 ± 0.4% of carbamazepine, 99.76 ± 0.01% of gemfibrozil and >99.9% of triclocarban from a mixture containing 0.2 μg L −1 of each by merely using 0.5 mg mL −1 of PNCS, thus out-performing commonly used scavengers.